Evaluation of glucose biosensors based on Prussian Blue and lyophilised, crystalline and cross-linked glucose oxidases (CLEC (R)) - de Mattos, I. L.; Lukachova, L. V.; Gorton, L.; Laurell, T.; Karyakin, A. A. (Elsevier B.V., 2001)
Glucose biosensors based on lyophilised, crystalline and cross-linked glucose oxidase (GOx, CLEC(R)) and commercially available lyophilised GOx immobilised on top of glassy carbon electrodes modified with electrodeposited Prussian Blue are critically compared. Two procedures were carried out for preparing the biosensors: (1) deposition of one layer of adsorbed GOx dissolved in an aqueous solution followed by deposition of two layers of low molecular weight Nafion(R) dissolved in 90% ethanol, and (2) deposition of two layers of a mixture of GOx with Nafion dissolved in 90% ethanol. The performance of the biosensors was evaluated in terms of linear response range for hydrogen peroxide and glucose, detection limit, and susceptibility to some common interfering species (ascorbic acid, acetaminophen and uric acid). The operational stability of the biosensors was evaluated by applying a steady potential of -50 mV versus Ag/AgCl to the glucose biosensor and injecting standard solutions of hydrogen peroxide and glucose (50 muM and 1.0 mM, respectively, in phosphate buffer) for at least 5 h in a flow-injection system. Scanning electron microscopy was used for visualisation of the Prussian Blue redox catalyst and in the presence of the different GOx preparations on the electrode surface. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Prussian Blue; hydrogen peroxide; cross-linked enzyme crystals; flow injection analysis